A hybrid life cycle assessment of the vehicle-to-grid application in light duty commercial fleet. (15th December 2015) - Zhao, Yang; Tatari, Omer
Abstract: The vehicle-to-grid system is an approach utilizing the idle battery capacity of electric vehicles while they are parked to provide supplementary energy to the power grid. As electrification continues in light duty vehicle fleets, the application of vehicle-to-grid systems for commercial delivery truck fleets can provide extra revenue for fleet owners, and also has significant potential for reducing greenhouse gas emissions from the electricity generation sector. In this study, an economic input–output based hybrid life cycle assessment is conducted to analyze the potential greenhouse gas emissions emission savings from the use of the vehicle-to-grid system, as well as the possible emission impacts caused by battery degradation. A Monte Carlo simulation was performed to address the uncertainties that lie in the electricity exchange amount of the vehicle-to-grid service as well as the battery life of the electric vehicles. The results of this study showed that extended range electric vehicles and battery electric vehicles are both viable regulation service providers for saving greenhouse gas emissions from electricity generation if the battery wear-out from regulation services is assumed to be minimal, but the vehicle-to-grid system becomes less attractive at higher battery degradation levels. Highlights: The commercial delivery trucks are studied as vehicle-to-grid service providers. Hybrid life cycle assessment is conducted to evaluate emission mitigation. Battery degradation level and corresponding emissions and cost are evaluated. Vehicle-to-grid service is shown to have significant emission saving effect.